2021
DOI: 10.1136/svn-2020-000737
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol for secondary stroke prevention: systematic review and meta-analysis

Abstract: BackgroundStroke is one of the leading causes of death worldwide. Cilostazol, an antiplatelet and phosphodiesterase 3 inhibitor, has not been clearly established for ischaemic stroke use. We aim to determine the efficacy and safety of cilostazol for secondary stroke prevention.MethodsMEDLINE, EMBASE, Cochrane Library, Web of Science and ClinicalTrials.gov were searched from inception to 25 September 2020, for randomised trials comparing the efficacy and safety of cilostazol monotherapy or dual therapy with ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…For example, in previous clinical trials and meta-analyses, cilostazol significantly reduced the risk of stroke recurrence and lower bleeding events compared to aspirin ( 40 , 41 ). Moreover, our current meta-analysis is in line with previous meta-analyses that found cilostazol to be more beneficial in patients with ischemic stroke ( 18 , 42 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, in previous clinical trials and meta-analyses, cilostazol significantly reduced the risk of stroke recurrence and lower bleeding events compared to aspirin ( 40 , 41 ). Moreover, our current meta-analysis is in line with previous meta-analyses that found cilostazol to be more beneficial in patients with ischemic stroke ( 18 , 42 ).…”
Section: Discussionsupporting
confidence: 90%
“…For example, in previous clinical trials and meta-analyses, cilostazol significantly reduced the risk of stroke recurrence and lower bleeding events compared to aspirin (40,41). Moreover, our current meta-analysis is in line with previous meta-analyses that found cilostazol to be more beneficial in patients with ischemic stroke (18,42). Although current meta-analysis and previous studies have shown the effectiveness and relative safety of using cilostazol as secondary prevention of stroke, research also shows that, even in non-Asian populations, cilostazol may have a significant potential for secondary stroke prevention.…”
Section: Discussionsupporting
confidence: 88%
“…Another meta‐analysis indicated that cilostazol significantly decreased ischemic stroke (RR, 0.69) or any stroke recurrence (RR, 0.64) and MACEs (RR, 0.67) 10 . Cilostazol did not affect mortality (RR, 0.90) or the rate of good functional outcome.…”
Section: Strokementioning
confidence: 99%
“…A recent meta‐analysis of 18 RCTs (N = 11 429) showed that cilostazol demonstrated a favorable safety profile, significantly decreasing the risk of intracranial hemorrhage (relative risk [RR], 0.46) and major hemorrhagic events (RR, 0.49), vs conventional antiplatelet therapies such as aspirin and clopidogrel 10 …”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…In addition, cilostazol may prevent recurrent ischemic stroke by improving endothelial function [ 44 ]. Cilostazol has been the focus of at least 18 randomized trials of secondary stroke prevention as outlined in a meta-analysis by Tan et al [ 45 ]. The dosing was typically 100 mg twice a day with or without aspirin.…”
Section: Cilostazolmentioning
confidence: 99%